Pengaruh Struktural Modal dan Kebijakan Dividen terhadap Nilai Perusahaan - Laura, Corry; Achmad, Daniel Noor (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
The firm value is the price that a potential buyer is willing to pay if the company will be sold. This value also a benchmark for investors to invest to obtain the desired profit. Dividend policy is to determine how much of the profits will be distributed as dividend to shareholders and how much as retained earnings. Capital structure is a proposition in determining the fulfillment of company spending where the proceeds are used for a combination or mixed that is the main source comes from the company's long-term funding consists of two main sources, from within and outside the company. The purpose of this study is to determine the relationship, the relationship closeness and influence between capital structure, dividend policy as a free variable against the value of the company as the dependent variable. Capital structure with DER indicators, dividend policy proxied by payout ratio, and the value of the company proxied by two indicators namely market value and intrinsic value per share. In this study the authors perform statistical testing either partially or simultaneously. The method of analysis used in this study are the correlation coefficient analysis (R) to identify the relationship among variables. The coefficient of determination analysis (R2) to determine the closeness of the relationship between independent variables and dependent variables, and regression coefficient analysis to measure the magnitude of the influence of independent variables against dependent variables. Besides, the trend analysis of the data was conducted to determine the development of data during the research period. Significant test conducted by F test and t test. The level of significance set in this study is 10%. The analysis found several important findings. Some are such as INTP R between capital structure and share price stood at 0.690 or at the level of a strong relationship. While on SMGR R is at 0,877 or very strong. Level of significance of both companies respectively 0.058 and 0.004. Meanwhile, Figures R between capital structure and intrinsic value reached 0.306 INTP or weak and insignificant (0.461). While on SMGR reached 0,841 or very strong with significance level of 0.009.